Diabetes mellitus triggers oxidative stress in the liver of alloxan-treated rats: A mechanism for diabetic chronic liver disease - Lucchesi, Amanda Natália [UNESP]; de Freitas, Natália Tavares [UNESP]; Cassettari, Lucas Langoni [UNESP]; Marques, Sílvio Fernando Guideti; Spadella, César Tadeu [UNESP] (FapUNIFESP (SciELO), 2013)
Purpose: To investigate whether Diabetes mellitus chemically induced by alloxan is capable of changing, in the long term, the oxidative balance in the liver tissue of rats. Methods: Sixty male Wistar rats, weighing 250-280g, were randomly distributed into two experimental groups: NG - 30 non-diabetic control rats; DG - 30 alloxan- induced diabetic rats without any treatment for the disease. Each group was further divided into three subgroups containing ten rats each, which were sacrificed after one, three and six months of follow-up, respectively. Blood glucose, urinary glucose, glycosylated hemoglobin and insulin were determined in the plasma of all animals at the beginning of the experiment and prior to all sacrifice periods. The concentrations of lipid hydroperoxides (HP) and the activity of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) were also measured in the liver tissue of all animals. Results: Rats from the DG group showed high levels of blood glucose, urinary glucose, and glycosylated hemoglobin, with significantly lower plasma insulin levels than those observed in NG rats (p<0.001). Diabetic animals also showed increased concentration of HP free radicals in the liver tissue as compared to those shown by NG animals after one, three and six months of follow-up. In contrast, the antioxidant activity of the enzymes SOD, CAT and GSH-Px was significantly reduced in all follow-up periods (p<0.01). Conclusions: Diabetes determines oxidative stress in the liver, which is characterized by increased concentration of reactive oxygen species (ROS) in tissue and significant reduction in their antioxidant defenses. Such oxidative unbalance in the liver cells may play a relevant role in the genesis of the diabetic chronic liver disease, including the non-alcoholic fatty liver disease and its occasional progression to steatohepatitis and cirrhosis.
Keywords: Alloxan; Diabetes Mellitus; Liver Diseases; Oxidative Stress; Rats; alloxan; catalase; free radical; glucose; glutathione peroxidase; glycosylated hemoglobin; insulin; lipid hydroperoxide; reactive oxygen metabolite; superoxide dismutase; animal experiment; animal model; animal tissue; chronic liver disease; controlled study; diabetes mellitus; male; nonhuman; oxidative stress; rat